Laser fabrication of MXene-based planar micro-supercapacitors - Li, Qian-Kun; Qi, Jin-Yong; Li, Bo; Li, Ke-Xue; Lin, Feng-Yuan; Tang, Ji-Long; Wei, Zhi-Peng (Frontiers in Chemistry, 2025)
This mini-review summarizes recent advances in MXene-based planar micro-supercapacitors fabricated by laser technologies. Laser ablation enables ultrafast maskless patterning, laser cutting achieves mechanically adaptive flexible arrays, and laser modification optimizes microstructure and surface chemistry. Representative studies, performance correlations, and prospects for scalable, high-energy-density MSCs are highlighted.